2021
DOI: 10.5455/medarh.2021.75.199-203
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum IL-6, IL-10, IL-12, and IL-23 Levels and Severity of Liver Cirrhosis

Abstract: Background: Liver cirrhosis contributes to high liver-related mortality globally. Systemic inflammation mediated by immune cells contributes to the progression of liver cirrhosis. Growing evidence shows that several pro- and anti-inflammatory cytokines might have an important role in liver cirrhosis. Objective: To evaluate the association between serum IL-6, IL-10, IL-12, and IL-23 levels and severity of liver cirrhosis. Methods: This observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…The study of Rey and Luo Ming shows that IL-6 is related to the severity of liver cirrhosis and to blood ammonia levels in patients with OHE. 22 , 23 However, our study did not get similar results, and we speculate that it may be because our study population (including various etiology) is different from previous reports.…”
Section: Discussioncontrasting
confidence: 92%
“…The study of Rey and Luo Ming shows that IL-6 is related to the severity of liver cirrhosis and to blood ammonia levels in patients with OHE. 22 , 23 However, our study did not get similar results, and we speculate that it may be because our study population (including various etiology) is different from previous reports.…”
Section: Discussioncontrasting
confidence: 92%
“…Interleukin-6 (IL-6) is an important cytokine regulating immune and inflammatory responses in the liver and is known to induce collagen synthesis [3, 4]. It also seems to correlate with the severity of LC [6]. In this study, we found that preoperatively determined baseline IL-6 levels might be a promising preoperative biomarker for LF.…”
Section: Discussionmentioning
confidence: 79%
“…Elevated IL-6 serum levels have been reported in patients with hepatitis B infection, acute hepatitis, and alcoholic LC [4]. Impaired hepatic removal of IL-6 is also reported in patients with LC [5] and appears to correlate with the severity of LC [6].…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 activates the STAT3 signaling pathway in HSC, producing type 1 collagen and promoting the development of liver fibrosis; the absence of IL-23 or the use of IL-17E (also known as IL-25) attenuates hepatic fibrosis; 24 and the level of IL-17 is positively correlated with the degree of liver damage in patients with hepatitis A. In hepatitis B (HBV) and hepatitis C virus (HCV) infections, IL-23 promoted chronic inflammation, IL-23 may enhance HCV infection mediated by dendritic cells and macrophages, 25 and IL-23 concentrations were significantly elevated in patients with cirrhosis caused by HBV and HCV infections, 26 there is a close correlation between IL-17 and IL-23 expression levels, and IL-23 may play a role in the pathogenesis of hepatitis B cirrhosis by inducing the production of IL-17 and the latter. In the present study, IL-17 and IL-23 concentrations increased significantly with increasing hepatic inflammation in patients and reached the highest concentrations in cirrhotic patients, similar to previous studies.…”
Section: Discussionmentioning
confidence: 99%